Global Security, Safety and Sustainability & e-Democracy 7th International and 4th e-Democracy, Joint Conferences, ICGS3/e-Democracy 2011, Thessaloniki, Greece, August 24-26, 2011, Revised Selected Papers - Georgiadis, Christos K.; Jahankhani, Hamid; Pimenidis, Elias; Bashroush, Rabih; Al-Nemrat, Ameer; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Conference on Global Security, Safety, and Sustainability (ICDS3), and of the 4th e-Democracy Joint Conferences (e-Democracy 2011) which were held in Thessaloniki in August 2011. The 37 revised full papers presented were carefully selected from numerous submissions. Conference papers promote research and development activities of innovative applications and methodologies and applied technologies.
Keywords: Computer science; Computer Communication Networks; Data protection; Biometrics; Computer Science; Computers and Society; Systems and Data Security; e-Commerce/e-business.; Information Systems Applications (incl. Internet).; Computer Communication Networks; Biometrics